NEW WESTERN CAPE TOURISM LEGISLATION - Patrick Vrancken (Obiter, 2022)
The Western Cape Province, and especially the area around the Cape Peninsula, is one of the major tourist attractions of South Africa. This has been the case for much longer than in many other parts of the country. As a result, the Western Cape tourism industry is comparatively very well established and developed to the extent that tourism is a very substantial element of the provincial economy and a significant focus area of the provincial government. This was reflected in the relative sophistication of the first tourism legislation passed in the province: the Western Cape Tourism Act (3 of 1997). However, a range of factors, including political and economic ones, led quickly to a reform process that produced a Western Cape Tourism Bill in 2000 (PG 5497 of 2000-05-17) as well as the CapeTown Tourism and Events Company in 2003. (An association incorporated under s 21 of the Companies Act (Registration Number 2003/0044604/08) and hereinafter referred to as “the Company”.) That process culminated with the passing of the Western Cape Tourism Act (1 of 2004), that repealed the 1997 Act (s 25) when it came into effect on 1 April 2004 (s 26 read with Proclamation 5/2004 in PG 6116 of 2004-03-19). The aim of this contribution is to discuss this new piece of legislation, comparing it wherever appropriatewith the 1997 Act and the 2000 Bill.